Cyanotoxins removal from the water: a review - Ferreira, Evaldo de Melo; Oliveira, Keila Castro (Revista Monografias Ambientais, 2017)
The aim of this work is to show the state-of-the-art about powdered activated carbon and cyanotoxins removal, normally used to avoid health problems in drinking water. The work is part of the PhD research of the second author. Brazilian government has one important law about the subject, named as ordinance 2.914, which provides procedures for water quality control and monitoring. In addition, the standards of portability. Problems caused by cyanotoxins are discussed as one the most dangerous for the public health. The problems linked with cyanobacteria for a long time have been neglected. Some of the problems caused for the presence of this toxins in the water are gastroenteritis, hepato-enteritis and other diseases of the liver and kidney, cancer, skin irritations, allergies, conjunctivitis, vision problems, muscle weakness, respiratory problems, asphyxia, seizures and in extreme cases death. Papers from different bases were consulted as materials in this research. The main bases were Scopus, Science Direct, and SciELO.